Targeting Trypanothione Metabolism in Trypanosomatids - González-Montero, María-Cristina; Andrés-Rodríguez, Julia; García-Fernández, Nerea; Pérez-Pertejo, Yolanda; Reguera, Rosa M.; Balaña-Fouce, Rafael; García-Estrada, Carlos (Molecules (Basel, Switzerland), 2024)
Infectious diseases caused by trypanosomatids, including African trypanosomiasis (sleeping sickness), Chagas disease, and different forms of leishmaniasis, are Neglected Tropical Diseases affecting millions of people worldwide, mainly in vulnerable territories of tropical and subtropical areas. In general, current treatments against these diseases are old-fashioned, showing adverse effects and loss of efficacy due to misuse or overuse, thus leading to the emergence of resistance. For these reasons, searching for new antitrypanosomatid drugs has become an urgent necessity, and different metabolic pathways have been studied as potential drug targets against these parasites. Considering that trypanosomatids possess a unique redox pathway based on the trypanothione molecule absent in the mammalian host, the key enzymes involved in trypanothione metabolism, trypanothione reductase and trypanothione synthetase, have been studied in detail as druggable targets. In this review, we summarize some of the recent findings on the molecules inhibiting these two essential enzymes for Trypanosoma and Leishmania viability.